If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -17) = -2(x + 14) Reorder the terms: 5(-17 + x) = -2(x + 14) (-17 * 5 + x * 5) = -2(x + 14) (-85 + 5x) = -2(x + 14) Reorder the terms: -85 + 5x = -2(14 + x) -85 + 5x = (14 * -2 + x * -2) -85 + 5x = (-28 + -2x) Solving -85 + 5x = -28 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -85 + 5x + 2x = -28 + -2x + 2x Combine like terms: 5x + 2x = 7x -85 + 7x = -28 + -2x + 2x Combine like terms: -2x + 2x = 0 -85 + 7x = -28 + 0 -85 + 7x = -28 Add '85' to each side of the equation. -85 + 85 + 7x = -28 + 85 Combine like terms: -85 + 85 = 0 0 + 7x = -28 + 85 7x = -28 + 85 Combine like terms: -28 + 85 = 57 7x = 57 Divide each side by '7'. x = 8.142857143 Simplifying x = 8.142857143
| 10x-x=14 | | 100x-10x=108 | | 100x-10x=11 | | 7a+23=3 | | x(5x^2+10x-15)=0 | | y=px+a | | y=px | | 0=6x^2+10x-16 | | 6(5x+2)=36x+10-2(3x-6) | | 13-3y+3y=15 | | 4(x)2=100 | | 16x+11y=120 | | (1-7z)(5)= | | (x+0.34)(x+.23)=2 | | X^4+116x^2+1600=0 | | -3x+3y-12=0 | | (-4-3b)(-8)= | | 8x-4=7x-9 | | 2(4x+7)=-47+53 | | 3.50/103.5 | | -3x+23=5-2(x-4) | | 5x-19=-34 | | g(-5b)=4x+3 | | 5x-19=34 | | (2x+3)(x^2+1)=(-3x-7)(x^2+1) | | 2b^2+6b=20 | | 9x+2+7x+18=180 | | -31+19= | | -2p-5(6-2p)=6(p-6)-10 | | -(-2y-6)+10= | | 3x+4(2x+1)=81 | | 6-4z+2=5z-2-z |